Studies on Nitrofuran Contamination in Exportable Shrimp and Prawn Products (Progressive Agriculture, 2013)
For the last few years, several consignments of frozen prawn and shrimp from Bangladesh have been rejected by the EU and USA due to presence of nitrofuran drugs. We have investigated the source of nitrofuran drugs in shrimp and prawn through participatory stakeholder based approach. Survey in greater Mymensingh region revealed that most of the hatchery operators and prawn farmers did not know about the devastating effect of nitrofuran on prawn while survey in Coxs Bazar and Khulna revealed that most of the hatchery operators knew about the nitrofuran drugs but they kept mum on nitrofuran related issues. A series of antibiotics sold in local veterinary drug shops of Coxs Bazar and Khulna were found to be used in shrimp hatcheries. While conducting stakeholder based dialogue in Khulna and Coxs Bazar, hatchery operators were directly blamed by shrimp/prawn farmers, depot holders and processors for using nitrofuran drug. Many hatchery technicians mentioned that they used nitrofuran drugs in the hatcheries 5-6 years back, much before than it was declared banned on shrimp products, but at present they were not using it. While asking about the unlabelled drugs using in their hatcheries, they did not respond but mentioned the efficacy of nitrofuran in the survival of shrimp/prawn PL and promotion of their growth. From the participatory stakeholder based study it was understood that both the prawn/shrimp hatchery and poultry feed/fish feed used as shrimp/prawn feed in grow out ponds might be the possible sources of contamination of nitrofuran drugs in exportable shrimp/prawn products.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16866 Progress. Agric. 20(1 & 2): 143 151, 2009